2021
DOI: 10.26434/chemrxiv.14230406.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Promotion and Tuning of the Electrochemical Reduction of Hetero- and Homobimetallic Zinc Complexes

Abstract: Compounds containing multiple metals attract significant interest due to the useful redox and reactivity properties of such species. Here, the electrochemical properties of a family of macrocyclic complexes that feature a zinc(II) center paired with a second redox-inactive metal cation in heterobimetallic (Na+, Ca2+, Nd3+, Y3+) motifs or a homobimetallic (Zn2+) motif have been investigated. The new complexes were prepared via a divergent strategy, isolated, and structurally characterized by single-crystal X-ra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…7 One especially vigorous area of investigation centers on use of secondary redox-inactive metals to tune the chemical properties of primary redox-active metal centers, 8,9,10 an approach of particular interest to us considering its versatility. 11,12,13 However, a unifying theme of all this work is the bringing together of two metals selectively, enabling studies of their individual roles in observed reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…7 One especially vigorous area of investigation centers on use of secondary redox-inactive metals to tune the chemical properties of primary redox-active metal centers, 8,9,10 an approach of particular interest to us considering its versatility. 11,12,13 However, a unifying theme of all this work is the bringing together of two metals selectively, enabling studies of their individual roles in observed reactivity.…”
Section: Introductionmentioning
confidence: 99%